Diversity, Inclusion, and Decolonization: Practical Tools for Improving Teaching, Research, and Scholarship - Day, Abby 1956-; Lee, Lois (Research associate); Thomas, Dave S. P.; Spickard, James V. (Bristol Bristol University Press, 2022)
Despite progress, the Western higher education system is still largely dominated by scholars from the privileged classes of the Global North. This book presents examples of efforts to diversify points of view, include previously excluded people, and decolonize curricula.What has worked? What hasn’t? What further visions do we need? How can we bring about a more democratic and just academic life for all?Written by scholars from different disciplines, countries, and backgrounds, this book offers an internationally relevant, practical guide to ‘doing diversity’ in the social sciences and humanities and decolonising higher education as a whole.
Introduction: Why Diversity, Inclusion, and Decolonization Matter / Abby Day, Lois Lee, Dave S.P. Thomas, and James Spickard -- Part I: Changing Universities; Negotiating Diversity, a Personal Reflection / Martin Stringer -- Demystifying the ‘Decolonising’ and ‘Diversity’ Slippage: Reflections from Sociology / Ali Meghji, Seetha Tan, and Laura Wain -- Doing Diversity Inclusively: ‘East Asians’ in Western Universities / Lin Ma -- This Island’s Mine: University Teaching as Inclusive Dramaturgy / Danny Braverman -- Emergent Tensions in Diversity and Inclusion Work in Universities: Reflections on Policy and Practice / Samantha Brennan, Gwen Chapman, Belinda Leach, and Alexandra Rodney -- Part II: Diversifying Curricula; How ‘Diverse’ is Your Reading List? Tools, Tips, and Challenges / Karen Schucan Bird -- Perceptions, Expectations, and Pluralised Realities: Reflections on Building Staff–Student Partnerships Through a Reading List Review / Dave S.P. Thomas -- Decolonizing Research Methods: Practices, Challenges, and Opportunities / Sara Ewing -- Towards an Intersectional Feminist Pedagogy of Gender-Based Violence - Denise Buiten, Ellen Finlay, and Rosemary Hancock -- Part III: Diversifying Research and Scholarship; How Would a World Sociology Think? Towards Intellectual Inclusion / James Spickard -- Whom We Cite: A Reflection on the Limits and Potentials of Critical Citation Practices / Januschka Schmidt -- Scholarship in a Globalized World: The Publishing Ecosystem and Alternatives to the Oligopoly / Paige Mann -- Part IV: Overcoming Intellectual Colonialism; Dealing with the Westernisation of Chinese Higher Education: Evidence from a Social Science Department / Fabio Bolzonar -- Opportunities and Challenges in Integrating Indigenous Peoples and Cultural Diversity in International Studies / Gretchen Abuso -- Decolonial Praxis beyond the Classroom: Reflecting on Race and Violence / Federico Settler -- Epilogue: What We Have Learned / Abby Day, Lois Lee, Dave S.P. Thomas, and James Spickard
Includes bibliographical references and index.
Keywords: Education; Teaching; Multiculturalism; Social science